2013
DOI: 10.1002/hep.26262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel serum biomarkers of hepatocellular carcinoma using glycomic analysis

Abstract: The altered N-glycosylation of glycoproteins has been suggested to play an important role in the behavior of malignant cells. Using glycomics technology, we attempted to determine the specific and detailed N-glycan profile for hepatocellular carcinoma (HCC) and investigate the prognostic capabilities. From 1999 to 2011, 369 patients underwent primary curative hepatectomy in our facility and were followed up for a median of 60.7 months. As normal controls, 26 living Japanese related liver transplantation donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 36 publications
2
70
1
1
Order By: Relevance
“…In this study, we demonstrated the importance of the total glycomics of HD transgenic (R6/2) and WT mice (BCF1) using the glycoblotting method [35][36][37][38][39][40][41]47,56]. This technique enabled us to efficiently estimate the structure and quantify the total glycomes derived from the brain and serum glycoproteins and glycosphingolipids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we demonstrated the importance of the total glycomics of HD transgenic (R6/2) and WT mice (BCF1) using the glycoblotting method [35][36][37][38][39][40][41]47,56]. This technique enabled us to efficiently estimate the structure and quantify the total glycomes derived from the brain and serum glycoproteins and glycosphingolipids.…”
Section: Resultsmentioning
confidence: 99%
“…These include the study of conserved oligomeric Golgi (COG)-deficient patients and the increasing prevalence age and agerelated diseases identified via glycoform characterization of serum, plasma and CSF by using ESI-MS, affinity chromatography, and 2-DE followed by MS/MALDI-MS/DNA sequencer adapted-fluorophore assisted carbohydrate electrophoresis (DSA-FACE) and HILIC-HPLC [13]. Moreover, glycosylation changes in non-invasive bodily fluids, inter alia, serum, urine, plasma glycomes and on individual glycoproteins have been identified as promising biomarkers for the detection of prostate cancer [28], hepatocarcinoma cancer (HCC) and cirrhosis of the liver [35,36], pancreatic cancer [37], ulcerative colitis [38], and bladder cancer [39]. Measuring the degree of alteration of specific glycans in serum/plasma or whole blood has helped to provide a novel, noninvasive method for determining prognosis in cases of cancer and the existence of specific altered glyco-phenotypes, which might represent risk factors for the sequela of certain diseases [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, expression of N-acetylglucosaminyltransferase-III and -V is increased in hepatocellular carcinoma (9,10). An N-glycan profiling study identified novel N-glycan structures in serum as prognostic markers of hepatocellular carcinoma (11). In addition, a-1,6-fucosyltransferase can generate fucosylated a-fetoprotein (AFP), which provided a more accurate diagnosis of hepatocellular carcinoma from chronic liver diseases (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Serum glycomic studies to discover novel glycan cancer biomarkers have been highlighted (Adamczyk et al 2012 ). Numerous glycan tumor marker candidates for various cancers, including liver (Kaji et al 2013 ;Kamiyama et al 2013 ;Wu et al 2012 ;Tang et al 2010 ;Goldman et al 2009 ;Comunale et al 2009 ;Tanabe et al 2008 ;Ressom et al 2008 ), ovary (Biskup et al 2013 ;Hua et al 2013 ;Alley et al 2012 ;Abbott et al 2010 ;Leiserowitz et al 2008 ), pancreas (Li et al 2009 ;Okuyama et al 2006), breast (de Leoz et al 2011Alley et al 2010 ;Zeng et al 2010 ;Storr et al 2008 ;Abd Hamid et al 2008 ;Kyselova et al 2008 ;Kirmiz et al 2007 ), prostate , lung (Arnold et al 2011 ), colorectum (Zhao et al 2012 ), bile duct (Silsirivanit et al 2011 ), and esophagus ) cancers, have been reported. Most of these glycomic analyses have been carried out by newly developed high-throughput platform technologies, such as mass spectrometry-based methods and lectin-based methods, which have enabled the effi cient analysis of large cohorts of samples.…”
Section: Glycomic Studies On Serum Of Cancer Patientsmentioning
confidence: 98%